Influencia de las relaciones parentales en el estado de ánimo de una estudiante - Moncerrate Ochoa, Leydi Diana (2020)
The relationship of the couple a set of adolescent habits absorbed by the social norms that are established in the environment can also be considered that the emotional and behavioral manifestations that the adolescent has made in the environments in which he is immersed that can be said What is the social and family school environment? This case was carried out in the Barreiro educational unit of the Babahoyo canton in the province of Los Ríos and this has several bibliographical references that are reflected in the development of this case in which it can be extended a little more knowledge about these two variables. This is a very important case Since the 14-year-old girl in which she held 3 work sessions in which she applied the cognitive behavioral technique to be able to detect the dysfunctional thoughts that were affecting her mood, there could be an improvement After this application in which the parents were also recommended to have a good relationship so that it does not influence Isabel's mood.